Storytelling som marknadsföringsstrategi : AB Enaforsholm - Sellberg, Linnéa; Sjögren, Pernilla (SLU/Dept. of Economics, 2012)
The marketing strategies discussed in today’s literature are often developed for larger compa-nies and are therefore poorly fitted for smaller businesses with little resources, such as the small resort Enaforsholm Fjällgård in Jämtland. Hence, this paper focuses on presenting and discussing the marketing strategy storytelling and whether it is applicable to Enaforsholm Fjällgård. This mountain resort was given to the Royal Swedish Academy of Agriculture and Forestry (KSLA) in 1937 as a trust fund to be managed in the spirit of the grantor A.W. Bergsten. It is, in large, reserved preserved in its historic condition. The premise is that the story of Bergsten and his life could be used in the external marketing to create a concept that creates greater value and attracts customers. The story tells of how Bergsten became a suc-cessful businessman but only found happiness when he, due to poor health, started visiting the mountains where he found his summer home at Enaforsholm. This paper will show how the use of stories in marketing fits well with traditional marketing theories and consumption behavior theory. It will also show the conclusion that the benefits of storytelling out ways the disadvantages. Another conclusion is that the story of the grantor can be used in marketing purposes and that this story can be implemented as a concept for Enaforsholm Fjällgård.